Ответ:
Пошаговое объяснение:
1)-32,3 * 7 10/13 + 2 3/13*(-32,3) = -32,3 *(7 10/13+2 3/13) = -32,3 * 10 = -323
2)1,6*(-5,3) - 2,4*(-5,3) - 4 4/5 * 5,3 = -5,3*(1,6-2,4 + 4,8) = -5,3*4 = -21,2
3) -5,6 * 4 2/3 + 6 47/48 * 5,6 + 2 5/16*(-5,6)b= -5,6*(4 2/3 - 6 47/48 + 2 5/16) = -5,6*(4 32/48 - 6 47/48 + 2 15/48) = -5,6 * 0 = 0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1)-32,3 * 7 10/13 + 2 3/13*(-32,3) = -32,3 *(7 10/13+2 3/13) = -32,3 * 10 = -323
2)1,6*(-5,3) - 2,4*(-5,3) - 4 4/5 * 5,3 = -5,3*(1,6-2,4 + 4,8) = -5,3*4 = -21,2
3) -5,6 * 4 2/3 + 6 47/48 * 5,6 + 2 5/16*(-5,6)b= -5,6*(4 2/3 - 6 47/48 + 2 5/16) = -5,6*(4 32/48 - 6 47/48 + 2 15/48) = -5,6 * 0 = 0